Recent Advances in Green Synthesis of Functionalized Quinolines of Medicinal Impact (2018‐Present). Issue 40 (25th October 2022) - Yadav, Pooja; Bhalla, Aman
Abstract: The synthetic chemists are awakening to make substantial development in finding safer drugs against the rising communicable and non‐communicable type of diseases. By replacing traditional methods to more sustainable and greener approaches, multicomponent reactions are the rapid and efficient tool for the synthesis of organic molecules of structural diversity and complexity. Heterocyclic chemistry transforms small set of precursors into series of molecules by multicomponent domino reactions. This review covers recent trends of last five years (2018–2022) in construction of potentially drug‐like quinoline derivatives. The methods discussed here are preferable over conventional approaches being inexpensive, consuming lesser reaction time, atom economical, saving energy and manpower while avoiding toxic reagents/materials, chemical wastes and are environmental/occupational benign. The contributions covered here involve metallic, metal free strategies and other catalytic pathways including nanoparticles, ionic liquids and photocatalysis which are operationally safe and reliable. Abstract : The present study reveals progress in green synthesis of core quinolines in recent decade. Environment compatible synthetic methods and techniques have been discussed using one‐pot assembly for multicomponent reactants. Diverse catalytic systems such as metallic/non‐metallic/nanoparticles/photo‐catalysts and many more have been employed for successful synthesis of desired and biologically valuable quinoline molecules.